(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
This article investigates major points of the importance of using modern pedagogical technologies in foreign language teaching. Moreover, this has been pointed on both theoretical and practical aspects of the research analyses. Author concludes with the final steps of the importance of using modern pedagogical technologies in foreign language teaching.